Voting for direct democratic participation: Evidence from an initiative election - Felix Arnold; Ronny Freier; Magdalena Pallauf; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2015)
We study a constitutional change in the German State of Bavaria where citizens, not politicians, granted themselves more say in politics at the local level through a state initiative election. This institutional setting allows us to observe revealed preferences for direct democracy and to identify factors which explain these preferences. Empirical evidence suggests that support for direct democracy is related to dissatisfaction with representative democracy in general rather than with an elected governing party.
Keywords: D72; H70; 330; Direct Democracy; Voting; Initiative; Parties